Luminescent Anticancer Acenaphtho[1, 2‐b]quinoxaline: Green Synthesis, DFT and Molecular Docking Studies, Live‐Cell Imaging and Reactivity towards Nucleic Acid and Protein BSA. Issue 19 (22nd May 2018) - De, Sourav; Subran, Sunisha Kottukulam; Ramasamy, Selva kumar; Banerjee, Subhasis; Paira, Priyankar; Kalleshappa, Ashok Kumar Somanahalli
Abstract: A series of acenaphtho[1, 2‐b]quinoxaline derivatives 3 a ‐3 j were prepared using single step condensation of acenaphthoquinone with different o ‐phenylene diamine derivatives on water under sonication. Interaction of 9‐fluoro acenaptho[1, 2‐b]quinoxaline (3 g ) with calf‐thymus DNA has been explored by using absorption and emission techniques. The compound 3 g cleave DNA oxidatively without any exogenous additives. The protein binding ability has been observed by quenching of tryptophan emission in the presence of 3 g using bovine serum albumin (BSA) as model protein. The DNA and protein docking study suggests that most of the quinoxaline derivatives interact with DNA through the minor groove and occupies the active site of the protein favorably by hydrogen bonding. The density functional calculations carried out on 3 a ‐3 j have shown that electron‐rich regions in the highest occupied orbital are localized on the quinoxaline moiety. Live‐cells imaging result showed the clear evidence of strong cellular uptake of compound 3 g in HeLa cell line. The MTT assay concluded that compounds:9, 10‐dichloroacenaptho[1, 2‐b]quinoxaline (3 d ), 9‐bromoacenaptho[1, 2‐b]quinoxaline (3 e ), 3 g and 9‐chloro‐10‐fluroacenaptho[1, 2‐b]quinoxaline (3 j ) were exhibited highly selective cytotoxicity profiles in two cancer cell lines such as MCF‐7 and HeLa with respect to normal HEK‐293. Among them, compound 3 g displayed high potency and selectivity in all the cell lines. Abstract : A novel acenaphtho[1, 2‐b]quinoxaline scaffolds have been developed for cancer theranostic application. The potent compound 9‐fluoro acenaptho[1, 2‐b]quinoxaline cleave DNA oxidatively without any exogenous substances. Live‐cells imaging result indicate the strong cellular uptake of compound in HeLa cell line. The MTT assay of potent compound exhibited highly selective cytotoxicity profiles in two cancer cell lines and cytotoxicity level was suddenly decreased in absence of electron withdrawing group in quinoxaline ring.